2020
DOI: 10.3390/ani10040698
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of Avian Dendritic Cells under the Induction of Prebiotics

Abstract: Although the immunomodulatory properties of prebiotics were demonstrated many years ago in poultry, not all mechanisms of action are yet clear. Dendritic cells (DCs) are the main antigen-presenting cells orchestrating the immune response in the chicken gastrointestinal tract, and they are the first line of defense in the immune response. Despite the crucial role of DCs in prebiotic immunomodulatory properties, information is lacking about interaction between prebiotics and DCs in an avian model. Mannan-oligosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 151 publications
(182 reference statements)
0
8
0
Order By: Relevance
“…Dendritic cells (DCs) are antigen-presenting cells (APCs) with a unique ability to induce both innate and highly antigen-specific acquired immunity [48] through immune cell proliferation and cytokine production [49]. Because of these abilities, DCs are often called "nature's adjuvants" [50] and are recognized as an important component of any vaccination strategy.…”
Section: Role Of Cell-mediated Immune Responsementioning
confidence: 99%
“…Dendritic cells (DCs) are antigen-presenting cells (APCs) with a unique ability to induce both innate and highly antigen-specific acquired immunity [48] through immune cell proliferation and cytokine production [49]. Because of these abilities, DCs are often called "nature's adjuvants" [50] and are recognized as an important component of any vaccination strategy.…”
Section: Role Of Cell-mediated Immune Responsementioning
confidence: 99%
“…The main products of microbial fermentation of carbohydrates are short-chain fatty acids (SCFAs) and gases [ 22 ]. Chitosan oligosaccharides (COS) and the degradation of chitosan also have prebiotic-like effects in vitro [ 113 ] and in vivo [ 114 , 115 ]. Recent research has shown that the absorption of low molecular (low-MW) chitosan oligosaccharides (MWs of 13 kD and 22 kD) is higher than that of chitosan in the intestine, while high-MW chitosan oligosaccharides (230 kD) are non-absorbable in in vitro models [ 86 ].…”
Section: Alterations Of Gut Microbiota By Chitosan and Its Derivatmentioning
confidence: 99%
“…The β-glucans and MOS contained in Alphamune G have a high take-up by poultry producers and veterinarians. They are used in feed to increase the effectiveness of vaccinations and prophylactically during periods of increased susceptibility of birds to certain diseases, as well as during treatment and recovery after diseases associated with immunosuppression (14,18,24,41,52,55). Their use reduces the amount of antibiotics administered to birds throughout the production cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Their use reduces the amount of antibiotics administered to birds throughout the production cycle. Beta-1,3/1,6 glucans stimulate macrophages to produce increased amounts of cytokines and eicosanoids, which trigger the proliferation and activity of CD4 + and CD8 + T lymphocytes and antibody synthesis ( 1 , 13 , 54 , 55 ). It has been demonstrated that MOS clearly modulate immune processes at the level of the gut-associated lymphoid tissue, which may confer significant health benefits ( 24 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation